2014
DOI: 10.1186/bf03352423
|View full text |Cite
|
Sign up to set email alerts
|

Plasmaspheric electron content in the GPS ray paths over Japan under magnetically quiet conditions at high solar activity

Abstract: Vertical total electron content (GPS-TEC) data obtained from the dual-frequency GPS receiver network (GEONET) in Japan are compared with those calculated using the Sheffield University plasmasphere-ionosphere model (SUPIM). The model is also used to estimate the electron content in the plasmaspheric sections of GPS ray paths for the three seasons of high solar activity (F10.7 = 165) under magnetically quiet conditions. According to the estimates, the plasmaspheric sections of vertical GPS ray paths over Japan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…This effect is even more pronounced during nighttime at the solar activity minimum, where the plasmaspheric contribution to TEC can exceed the ionospheric one (Lunt et al, 1999a, b;Cherniak et al, 2012;Klimenko et al, 2015c). In fact, the TEC variability depends on the lower and topside ionosphere as well as the plasmasphere (Balan et al, 2002;Gulyaeva and Gallagher, 2007;Yizengaw et al, 2008;Cherniak et al, 2012;Lee et al, 2013;Zakharenkova et al, 2013;Klimenko et al, 2015b, c;Lei et al, 2015). Previous studies have demonstrated both the positive correlation between TEC and foF2 at high and middle latitudes during many storm events and no evident correlation between TEC and foF2 at low and middle latitudes during some storms (Maruyama et al, 2004;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is even more pronounced during nighttime at the solar activity minimum, where the plasmaspheric contribution to TEC can exceed the ionospheric one (Lunt et al, 1999a, b;Cherniak et al, 2012;Klimenko et al, 2015c). In fact, the TEC variability depends on the lower and topside ionosphere as well as the plasmasphere (Balan et al, 2002;Gulyaeva and Gallagher, 2007;Yizengaw et al, 2008;Cherniak et al, 2012;Lee et al, 2013;Zakharenkova et al, 2013;Klimenko et al, 2015b, c;Lei et al, 2015). Previous studies have demonstrated both the positive correlation between TEC and foF2 at high and middle latitudes during many storm events and no evident correlation between TEC and foF2 at low and middle latitudes during some storms (Maruyama et al, 2004;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This reveals that the shape of the IRI derived vertical electron density profile is contributing a major input to the deviations in TEC. It should be mentioned here that the TEC values from both reconstructed profiles and IRI-2007 profiles are expected to be lower than that of GPS-TEC, as the integration is done from the bottom side to only up to 1000 km altitude, whereas, the GPS-TEC also accounts for the plasmaspheric content up to GPS altitudes (∼22 000 km) (Balan et al, 2002). However, the observed differences between the GPS-TEC and the TEC derived from IRI-2007 profiles are quite larger and in a few cases TEC from reconstructed profile is larger than that of the GPS-TEC.…”
Section: Comparison Of the Total Electron Contentmentioning
confidence: 99%
“…Electron contents above 1,000 km altitude are extrapolated to match the results reported by Balan et al (2002). Solar maximum equinox −2.0 ± 0.1 TECU −2.5 ± 1.4 TECU −1.9 ± 2.7 TECU Solar maximum winter −0.4 ± 0.9 TECU 0.0 ± 1.6 TECU 2.0 ± 2.9 TECU Solar maximum summer −2.8 ± 0.6 TECU −2.8 ± 0.9 TECU −2.9 ± 1.7 TECU Solar minimum equinox −0.6 ± 0.5 TECU −1.5 ± 1.3 TECU −2.6 ± 2.3 TECU Solar minimum winter −0.6 ± 0.5 TECU −0.9 ± 0.8 TECU −0.8 ± 1.3 TECU Solar minimum summer −0.6 ± 0.3 TECU −1.2 ± 0.6 TECU −2.3 ± 1.5 TECU Averages and standard deviations of difference between the estimated vertical TEC and the corresponding vertical TEC given by the model based on the IRI-95 model over three locations for three seasons under solar maximum and minimum conditions.…”
Section: Model Simulationmentioning
confidence: 99%
“…According to Lunt et al (1999b), the plasmaspheric electron content in the European sector is 2 TECU at the solar minimum while the corresponding value in the American sector is about 0.5 TECU. Balan et al (2002) have obtained the plasmaspheric electron contents over Japan by comparing TEC obtained from the GEONET with that derived from SUPIM for different seasons at high solar activity. According to their study, the plasmaspheric contribution to the GPS TEC is up to 12 TECU at high solar activity, which changes appreciably with season and latitude and very little with the time of day.…”
Section: Comparison With Mu Radar Observationsmentioning
confidence: 99%